Choledochal cysts: lessons from a 20 year experience. Issue 6 (December 1995) - Stringer, M D; Dhawan, A; Davenport, M; Mieli-Vergani, G; Mowat, A P; Howard, E R
Abstract : Cystic dilatation of the biliary tree is a rare congenital anomaly. To determine mode of presentation, diagnostic pitfalls, and long term outcome after surgery, 78 children (57 girls, 21 boys) with choledochal cyst treated between 1974 and 1994 were reviewed. Anatomical types were: Ic (n = 44), If (n = 28), IVa (n = 4), and V (n = 2); a common pancreaticobiliary channel was identified in 76% patients. Age at presentation ranged from 0-16 (median 2.2) years, six patients being diagnosed by prenatal ultrasonography. Of the 72 patients diagnosed postnatally, 50 (69%) presented with jaundice, associated with abdominal pain in 25 or a palpable mass in three, 13 (18%) presented with pain alone, and two (3%) with a palpable mass. The classic triad of jaundice, pain, and a right hypochondrial mass was present in only four (6%). Four children presented acutely after spontaneous perforation of a choledochal cyst, two presented with ascites and one cyst was discovered incidentally. Plasma and/or biliary amylase values were raised in 30 of 31 patients investigated for abdominal pain; seven had evidence of pancreatitis at operation. In 35 of 67 (52%) patients referred without previous surgery, symptoms had been present for more than one month, and in 14 of them for more than one year, before diagnosis. Delayed referral was due to misdiagnosis as hepatitis (n = 12), incomplete investigation of abdominal pain (n = 6), and failure to note the significance of ultrasonographic findings (n = 10). Two patients referred late died from liver failure. Of the 76 patients with type I or IV cysts, 59 underwent radical cyst excision and hepaticojejunostomy as a primary procedure and 10 as a secondary operation after previously unsuccessful surgery. Sixteen patients have been lost to follow up but most of the remainder are well after a mean period of 4.1 (0.1-13) years. Choledochal cysts are often misdiagnosed, but prognosis is excellent if radical excision is performed.